Operasi Vaginal Rejuvenation dalam Perspektif Islam - Nur Roikhana Zahro (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2015)
Vaginal Rejuvenation (sometime misspelled vaginal rejuvination) is a general term that refers to surgical procedures to help tighten and support the vagina and its structures. Women who want to enhance or improve sexual gratificationand suffer from stress urinary incontinence (involuntary loss of urine with laughing, coughing, sneezing, exercising etc.) can have this condition treated at the same time as the Vaginal Rejuvenation surgery. The main function of this sugery is about womens’ reproduction health. This technology of surgery according to Islamic law has not yet being discussed, about its appropriateness or legality. That is why in this paper I would like to discuss it.